Abrasion Behavior of Different Charcoal Toothpastes on Human Dentin When Using Electric Toothbrushes - Nadin Osmanaj; Svea Petersen; Michael Eisenburger; Andreas Greuling (MDPI AG, 2022)
The aim of this study was to investigate abrasion on human dentin after brushing with activated charcoal toothpastes. A self-designed brushing machine was used to brush five groups (Group A: Water, Group B: Sensodyne Pro Schmelz, Group C: Splat Blackwood, Group D: Curaprox Black is White, and Group E: Prokudent Black Brilliant) with electrically powered toothbrushes for 4 h. The abrasive dentin wear was calculated using profilometry data. Furthermore, thermogravimetric analyses and scanning electron microscopy were used to analyze the composition of the toothpastes. Mean dentin loss by brushing were (71 ± 28) µm (Splat Blackwood), (44 ± 16) µm (Curaprox Black is White), (38 ± 13) µm (Prokudent Black Brilliant), (28 ± 14) µm (Sensodyne Pro Schmelz), and (28 ± 13) µm (Water). Groups A/B/D/E and group C each lie in one subset, which is statistically different from the other subset according to a post hoc Tukey test (p = 0.05). Within the limitations, it can be concluded that the content of activated charcoal in charcoal toothpastes had little influence on the observed abrasive behavior, although one of the charcoal toothpastes showed the highest abrasion on dentin.